The Rationality of Illegal Street Vendors on HR. Soebrantas Street, Panam, Pekanbaru City - Izkil, Mohammad; Novarizal, Riky (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the rationality of illegal street vendors on Jalan HR. Soebrantas Panam. The method used is qualitative with a descriptive approach and a case study type, with data collection techniques through interviews, observations, and documentation of informants analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the rationality of illegal street vendors on Jalan HR. Soebrantas Panam is the result of a systematic cost-benefit calculation in accordance with the concept of Rational Choice Theory. The decision of illegal street vendors to continue trading in illegal locations is not simply a spontaneous or reckless act, but rather an adaptive strategy that arises from considering the risks of enforcement, economic opportunities, and the social conditions they face. Rational Choice Theory is able to comprehensively explain illegal behavior, both at the individual and collective levels. Illegal street vendors evaluate risks, assess profit opportunities, and adjust strategies based on their social and economic context. They balance financial gains with the risks of enforcement, utilize social networks to optimize survival opportunities, and make tactical adjustments based on previous experience. This strategy demonstrates that illegal street vendor behavior is the result of rational, adaptive, and systematic calculations.